2003
DOI: 10.3171/jns.2003.98.5.1136
|View full text |Cite
|
Sign up to set email alerts
|

Third ventriculostomy for internal hydrocephalus complicated by unrecognized subdural hygroma and hematoma: a case report of a patient treated by Dr. Walter Dandy

Abstract: The authors review the case of a patient treated by Dr. Walter Dandy. When the patient was a young child he underwent two right transtemporal third ventriculostomies during which he sustained an unrecognized contralateral subdural hygroma and a chronic subdural hematoma with a mild infantile hemiparesis. He was able to complete high school, albeit at a slower pace than usual. As an adult he held several limited employment positions, lived at home for several decades, and was later cared for at a nursing home f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The disadvantage of this method consisted besides of the occasional necessity to sacrifice the optic nerve also in the frequent occurrence of hygromas (King 2003). To overcome this problem Dandy preferred since 1933 a more posterior extradural subtemporal approach (Aschoff et al 1999, Dandy 1933, King 2003. It is reported that Dandy performed also 2 endoscopic inspections in children with hydrocephalus.…”
Section: First Clinical Applications Of Endoscopy In Neurosurgerymentioning
confidence: 99%
See 2 more Smart Citations
“…The disadvantage of this method consisted besides of the occasional necessity to sacrifice the optic nerve also in the frequent occurrence of hygromas (King 2003). To overcome this problem Dandy preferred since 1933 a more posterior extradural subtemporal approach (Aschoff et al 1999, Dandy 1933, King 2003. It is reported that Dandy performed also 2 endoscopic inspections in children with hydrocephalus.…”
Section: First Clinical Applications Of Endoscopy In Neurosurgerymentioning
confidence: 99%
“…This was achieved anatomically by means of an open ventriculostomy perforating the lamina terminalis from a temporopolar approach (Aschoff et al 1999;King 2003). The disadvantage of this method consisted besides of the occasional necessity to sacrifice the optic nerve also in the frequent occurrence of hygromas (King 2003). To overcome this problem Dandy preferred since 1933 a more posterior extradural subtemporal approach (Aschoff et al 1999, Dandy 1933, King 2003.…”
Section: First Clinical Applications Of Endoscopy In Neurosurgerymentioning
confidence: 99%
See 1 more Smart Citation